BUDAYA SEKOLAH DAN PEMBINAAN AKHLAK SISWA SMP AL-KAUTSAR TANJUNGPINANG - Ramandha Rudwi Hantoro (Jurusan Tarbiyah dan Pendidikan, 2021)
This study aims to determine the relationship between the influence of school culture on the moral development of students at SMP Al-Kautsar, Tanjungpinang City. The population in this study were all students of SMP BP Al-Kautsar Tanjungpinang by taking all students as respondents, totaling 100 students. This research data collection method using questionnaire data and interviews. The hypothesis of this study is that there is a significant relationship between school culture (x) and Moral Development (Y). The results showed that there was a positive influence (0, 481) with a